Literasi Sains dan Digital dalam Pembelajaran IPA Melalui Window Shopping Berbantuan Flyer Maker - Makhdum, Muhammad (Jurnal Didaktika Pendidikan Dasar, 2022)
The scientific and digital literacy of grade VIII-B students at SMP Negeri 2 Tambakboyo in science learning is still very low. The results of observations showed that students’ reading interest in scientific information was very low, students had not been able to process and present the information they received well, and students lacked confidence when presenting in front of the class. To overcome this problem, the authors designed science learning with a scientific approach through window shopping assisted flyer maker aplication. The research method uses quantitative descriptive analysis. Observation results show that students’ ability to find scientific information through digital devices shows a score of 2.79 (good), finding scientific information from relevant and reliable digital sources shows an average of 2.54 (good), presenting scientific information in writing shows a number 2.41 (good), and presenting scientific information verbally shows a score of 1.9 (enough).